👤

9. Rezolvă în mulțimea numerelor întregi ecuațiile: a) (3x-2):5+3=2; b) (2 + 3(x-1)]-8=-3; c) 10-3-[1-20x - 7)] = -5; d) [8+3(1-x)] - (-2)+1 = -3; e) 3-[(2x+4)-2-5] +7=-20; f) 2-[5 (x+1)+3]: 2 = 13; g) (-6) [1-3-(x+2)]-4=26; h) [9-4-(x+1)+3]: (-3)-(-1)=-7.​

Răspuns :

2*3*(-5)*(-3)*(-20)*13*26*(-7)= =6*15*(-260)*(-182)

=90*(-260)*(-182)

= -23400*(-182)

= 4258800

6*(-5)*(-3) * (-20)* 13*26*(-7)=

= -30*(-3)*(-20)*13*26*(-7)

=90* (-20)*13*26*(-7)

=-1800*13*26*(-7)

= -23400*26*(-7)

= -608400*(-7)

= 4258800